Ação anulatória de sentença arbitral doméstica e impugnação à homologação de sentença arbitral estrangeira: preclusão, comportamento contraditório e renúncia - Vaz, Paula Akemi Taba (2023)
The purpose of this thesis is to analyze whether certain hypotheses of filing an annulment of a domestic arbitral award or of contesting the recognition of a foreign arbitral award are subject to preclusion in accordance with article 12, III and article 20 of the Brazilian Arbitration Law, or to dismissal due to violation of good faith, prohibition of contradictory behavior or waiver of the party's claim. Thus, the purpose of this thesis are the nullities and defects provided for by the Brazilian legislator for annulment of a domestic arbitral award and challenge of recognition of a foreign arbitral award, as well as the doctrinal understandings and judgments in which it is possible to verify the limits of the party to use these procedural instruments, when verification of preclusion, violation of the principle of good faith and prohibition of contradictory behavior, or waiver, mainly in a scenario of abuse of arbitration flexibility to avoid guerrilla tactics and avoid due process paranoia